Monte Carlo simulation of background characteristics of a HPGe detector operating underground in the Gran Sasso National Laboratory. (August 2017) - Breier, R.; Laubenstein, M.; Povinec, P.P.
Abstract: Monte Carlo (MC) simulation of background components of an ultra-low background high purity germanium (HPGe) detector operating in a deep underground laboratory was carried out. The results show that the background of the HPGe detector is about two orders of magnitude higher than the MC prediction when accounting only for cosmic-ray induced background. The difference is due to natural radioactivity in the parts surrounding the Ge detector. To get reasonable agreement between MC simulations and the experiment, a contamination in the parts surrounding the Ge crystal from 40 K, 208 Tl and 214 Bi of 0.1 mBq kg −1 was required to include in the simulations. Highlights: Monte Carlo simulations of muon-induced Ge detector background operating underground were carried out. Experimental and Monte Carlo simulated background spectra of Ge detector were compared. Experimental spectrum was by about two orders of magnitude higher than the simulated one. Contamination levels of 40 K, 214 Bi and 208 Tl surrounding the Ge detector were set at 0.1 mBq kg −1 .